PENTINGNYA SUMBER DAYA MANUSIA DALAM MENCAPAI EFEKTIVITAS KERJA - Febi Novianti E.42008053 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The aim of this thesis is to determine the effectiveness of the employment in the Archive and RegionalLibrary Office of Melawi District, especially in Archieve Departement. The title of this thesis raised by the issueof human resources in the Archive and Regional Library Office of Melawi District and until now there is still noway out solutions for it. The biggestt impact of this issue is make the effectiveness of the employment beingnegative.This study used a qualitative descriptive research model. This descriptive study aimed to describe theeffectiveness of the work in the Archive and Regional Library Office of Melawi District. The research locationis in Melawi District. The Subjects of thius research is employees in Archive and Regional Library Office ofMelawi District , especially the employees who associated with file management and staffing.The conclusion of this research is about the effectiveness working of employees who work in archivesdepartement, and it’s all because of the lack of ability to adjust levels, work performance and job satisfactionwho held by the employee. For that recommendation in this research is to improve human resources byimproving the knowledge, skills, and work ethic. Keywords: Archives, Effectiveness, and Human Resources